Acceptability and Necessity of Training for Optimal Personal Protective Equipment Use. (24th November 2016) - Doll, Michelle; Feldman, Moshe; Hartigan, Sarah; Sanogo, Kakotan; Stevens, Michael; McReynolds, Myriah; Masroor, Nadia; Cooper, Kaila; Bearman, Gonzalo
Abstract : Healthcare workers routinely self-contaminate even when using personal protective equipment. Observations of donning/ doffing practices on inpatient units along with surveys were used to assess the need for a personal protective equipment training program. In contrast to low perceived risk, observed doffing behaviors demonstrate significant personal protective equipment technique deficits. Infect Control Hosp Epidemiol 2017;38:226–229